THE IMPORTANCE OF AN INDIVIDUAL APPROACH IN EDUCATION AND UPBRINGING - Elshod Xusanov (Bright Mind Publishing, 2025)
This article examines the essential prerequisite for organizing individual educational work with children, which is understanding their fundamental intellectual and physiological characteristics. Among these, particular emphasis is placed on identifying the typological characteristics of the nervous system. The relevance of this issue is explained by the fact that, under conditions of globalization and technological development, applying the same pedagogical influences to children with different types of nervous activity may not be effective for each individual. As research methodology, analytical, comparative, and empirical approaches were employed. The results demonstrate that an individual approach to upbringing is one of the key factors in a child’s development. As the author’s scientific contribution, psychological factors influencing child upbringing were analyzed and practical recommendations were developed.
Keywords: Child, upbringing, individuality, methodology, psychological, nervous system, approach, education, society.